Pengembangan Green Organizational Citizenship Behavior dan Peran Kepuasan Kerja Serta Identifikasi Organisasi Dari Perspektif Green Human Resource Management di PT. Sungai Emas - Setiawan, Nicodimus Bayu; Suryani, Tatik (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
This study aims to determine the effect of Green Human Resource Management (GHRM) on Green Organizational Citizenship Behavior (GOCB) with Job Satisfaction and Organizational Identification as mediating variables, which was specifically conducted at PT. Sungai Emas. The sample in this study were 105 employees of PT. Sungai Emas with a sampling method using a questionnaire distributed to all divisions, the method used in this study is a quantitative method. Data was analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0 software. The results of this study indicate that Green Human Resource Management has a significant positive effect on Green Organizational Citizenship Behavior, Job Satisfaction, and Organizational Identification. In addition, Organizational Identification has a significant positive effect on Green Organizational Citizenship Behavior and mediates the effect of Green Human Resource Management on Green Organizational Citizenship Behavior. Meanwhile, Job Satisfaction does not affect Green Organizational Citizenship Behavior and also not as mediator of the relationship between Green Human Resource Management and Green Organizational Citizenship Behavior.